2021
DOI: 10.31224/osf.io/afxsb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Impacts of Speed Limit Increases on Rural Two-Lane Highways using Quantile Regression

Abstract: Understanding speed selection behavior of drivers following speed limits increases is critically important. To date, the literature has largely focused on freeways and the effects of speed limit changes on two-lane highways remains under researched. Prior research has generally focused on changes to mean speeds, though the speeds of both the highest and lowest drivers are also of great interest. This study investigates trends in free-flow travel speeds following 2017 legislation that increased the posted speed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Speed management has become an increasingly important topic over the prior decade as speed limits on rural highways have continued to rise across the United States. This is particularly the case in Michigan, where speed limits were raised from 55 to 65 mph on more than 900 mi of rural two-lane highways in 2017, and research has shown increases in travel speeds along these segments ( 18 ). In light of this, it is imperative to identify treatments that can safely and effectively assist drivers with the transition from a high-speed to low-speed road environment.…”
Section: Summary Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speed management has become an increasingly important topic over the prior decade as speed limits on rural highways have continued to rise across the United States. This is particularly the case in Michigan, where speed limits were raised from 55 to 65 mph on more than 900 mi of rural two-lane highways in 2017, and research has shown increases in travel speeds along these segments ( 18 ). In light of this, it is imperative to identify treatments that can safely and effectively assist drivers with the transition from a high-speed to low-speed road environment.…”
Section: Summary Conclusion and Recommendationsmentioning
confidence: 99%
“…This includes Michigan, where, in 2017, speed limits were increased from 55 to 65 mph on greater than 900 mi of rural state highways across the northern portions of the state. Recent research found that travel speeds increased by 2.8 to 4.8 mph in a sample of rural highway segments where the speed limit was raised to 65 mph ( 18 ). However, this prior research did not consider impacts to travel speeds within speed transition zones along those routes.…”
mentioning
confidence: 99%
“…This includes Michigan where, in 2017, speed limits were increased from 55 to 65 mph on more than 900 mi of rural state highways across the northern portions of the state ( 22 , 23 ). Recent research found that travel speeds increased by 2.8 to 4.8 mph along a sample of rural highway segments where the speed limit was raised from 55 to 65 mph ( 24 ). However, prior research has not explicitly considered the impact on travel speeds on curved portions of highway segments, where safety performance issues may be particularly exacerbated by increased travel speeds.…”
mentioning
confidence: 99%
“…With an increase in speed limit to 75 mph, one related concern is the effect on different groups of drivers. This is because the highest- and the lowest-speed drivers tend to behave differently when their driving environments are changed, leading them to lower or increase their speeds by different magnitudes ( 23 ). This results in greater variations in traffic speed, thus affecting traffic safety along the highway.…”
mentioning
confidence: 99%